2010
DOI: 10.1007/978-3-642-14998-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into Wave Propagation in Soft Tissue

Abstract: Abstract--In this article, the authors investigate wave propagation in soft-tissue matter with the aim of understanding the following: i) influence of nonlinear material properties of soft tissue on its mechanical response when subjected to transient loading and ii) mechanical response variation with respect to frequency and amplitude of the loading. To aid these investigations, reduced-order models are constructed taking into account available experimentally determined brain tissue properties and these models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…We measured the conductance of hist at various pH conditions to probe the available conformations of the molecule on gold. hist has two p K a values of 6.04 and 9.75, corresponding to the protonation of N3/N1 of imidazole and the amino side group, respectively. We have previously shown that imidazole can bridge the junction electrodes through N3 and N1 sites when deposited out of solution with a pH above the N3/N1 p K a , typically around neutral pH .…”
mentioning
confidence: 99%
“…We measured the conductance of hist at various pH conditions to probe the available conformations of the molecule on gold. hist has two p K a values of 6.04 and 9.75, corresponding to the protonation of N3/N1 of imidazole and the amino side group, respectively. We have previously shown that imidazole can bridge the junction electrodes through N3 and N1 sites when deposited out of solution with a pH above the N3/N1 p K a , typically around neutral pH .…”
mentioning
confidence: 99%